Green phosphorus-free nitrogen-free corrosion and scale inhibitor

Through the formulation and modification technology of polyaspartic acid and other components, the lack of performance and high cost of phosphorus-free nitrogen-free corrosion-resistant scale inhibitors under high hardness and high alkalinity water quality are solved, and high efficiency and environmental protection are achieved The corrosion inhibition and scale inhibition effect also improves the stability and scope of application of the product.

CN119240958AActive Publication Date: 2025-01-03NANJING CLEAN WATER TECH CO LTD

Patent Information

Application Number
CN202411499598.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-03
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing phosphorus-free nitrogen-free corrosion-resistant scale inhibitors are poor in scale inhibition under high hardness and high alkalinity water quality conditions, with high cost, limited scope of application, insufficient long-term stability, and insufficient research on synergistic effects, which limits its application effect. Improvement.

Method used

The formulation of components such as polyaspartic acid, hydrolyzed polymaleic acid, acrylic/hydroxypropyl acrylate copolymer, delta-valerollactam, sodium borate and zinc sulfate heptahydrate are adopted, and the composition is divided by modification technology and reasonable composition To achieve efficient corrosion inhibition and scale inhibition effects, and reduce production costs through optimized preparation processes.

Benefits of technology

It achieves excellent corrosion inhibition and scale inhibition effects under various water quality conditions, meets environmental protection requirements, reduces production costs, improves product consistency and stability, and is suitable for a variety of industrial water treatment scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240958A_ABST
    Figure CN119240958A_ABST
Patent Text Reader

Abstract

The invention discloses a green phosphorus-free and nitrogen-free corrosion and scale inhibitor, and relates to the technical field of energy-saving and environment-friendly water treatment agents. The corrosion and scale inhibitor is prepared from polyaspartic acid, hydrolytic polymaleic acid, acrylic acid / hydroxypropyl acrylate copolymer, polyepoxysuccinic acid, delta-valerolactam, sodium borate, zinc sulfate heptahydrate and benzotriazole according to a specific proportion. The preparation method comprises the following steps: preparing the modified polyaspartic acid, adding other components, mixing the modified polyaspartic acid and other components, adjusting the pH value, homogenizing, filtering, filling and the like. The corrosion and scale inhibitor has excellent corrosion and scale inhibition performance, the corrosion inhibition efficiency of the corrosion and scale inhibitor reaches up to 88.6%, and the scale inhibition rate ranges from 90.5% to 92.4%. Compared with a contrast agent, the efficient corrosion and scale inhibition performance is provided, meanwhile, the water treatment agent has the advantages of being environmentally friendly, economical and the like, and is a green water treatment agent with great application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy-saving and environmentally friendly water treatment agents, and in particular to a green phosphorus-free and nitrogen-free corrosion and scale inhibitor. Background Art

[0002] Water is the source of life and an indispensable resource in industrial production. However, in the industrial production process, water systems often face scaling and corrosion problems, which not only reduce the service life and operating efficiency of equipment, but also cause huge economic losses. In order to solve these problems, corrosion and scale inhibitors came into being and have been widely used in the field of industrial water treatment.

[0003] Traditional corrosion and scale inhibitors mainly include phosphorus compounds such as phosphates and organic phosphonates, as well as nitrogen compounds such as polyacrylamide. These compounds have good corrosion and scale inhibition effects, but they also have some serious environmental problems. The discharge of phosphorus-containing compounds into water bodies will lead to eutrophication of water bodies, causing algae to multiply in large numbers and destroying the water ecological balance. Nitrogen-containing compounds will increase the total nitrogen content of water bodies, which will also cause eutrophication problems. Therefore, the development of green and environmentally friendly corrosion and scale inhibitors has become a research hotspot and development trend in the current water treatment field.

[0004] In recent years, with the increasing awareness of environmental protection and the increasingly stringent relevant regulations, phosphorus-free and nitrogen-free corrosion and scale inhibitors have gradually become the focus of research. At present, the main phosphorus-free and nitrogen-free corrosion and scale inhibitors include the following categories:

[0005] Polycarboxylic acid compounds

[0006] Polycarboxylic acid compounds are an important class of phosphorus-free and nitrogen-free corrosion and scale inhibitors, mainly including polyacrylic acid (PAA), polymaleic acid (PMA), polyepoxysuccinic acid (PESA), etc. These compounds chelate with metal ions through carboxyl groups to form soluble complexes, thereby playing a role in scale inhibition. At the same time, carboxyl groups can also be adsorbed on the metal surface to form a protective film, which plays a role in corrosion inhibition. Polycarboxylic acid compounds have good biodegradability and are one of the most widely used green corrosion and scale inhibitors.

[0007] Polyamino acid compounds

[0008] Polyamino acid compounds, such as polyaspartic acid (PASP) and polyglutamic acid (PGA), are a new type of green corrosion and scale inhibitors. These compounds not only have good corrosion and scale inhibition properties, but also have excellent biodegradability and environmental friendliness. Polyamino acids can react with metal ions through carboxyl and amino groups, which can not only chelate metal ions but also form a protective film on the metal surface, thereby achieving the dual functions of corrosion and scale inhibition.

[0009] Natural polymer compounds and their derivatives

[0010] The use of natural polymer compounds and their derivatives as corrosion and scale inhibitors has been one of the research hotspots in recent years. Common natural polymers include starch, cellulose, chitosan, etc. These compounds can enhance their corrosion and scale inhibition properties through chemical modification, such as carboxymethylation and sulfonation. Natural polymer compounds are widely available, inexpensive, and have good biodegradability. They are highly potential green corrosion and scale inhibitors.

[0011] Inorganic silicon compounds

[0012] Inorganic silicon compounds, such as silicates and metasilicates, are also an important class of phosphorus-free and nitrogen-free corrosion and scale inhibitors7. These compounds inhibit corrosion by forming a dense silicate protective film on the metal surface. At the same time, silicate ions can also react with metal ions such as calcium and magnesium to form silicate complexes that are not easy to deposit, thereby inhibiting scale. Inorganic silicon compounds have good thermal and chemical stability and are suitable for high temperature and high pressure working conditions.

[0013] Organoboron compounds

[0014] Organoboron compounds, such as borates and polyborates, are new green corrosion and scale inhibitors that have been studied in recent years8. These compounds inhibit corrosion by forming a borate protective film on the metal surface. At the same time, borate ions can also react with metal ions such as calcium and magnesium to form soluble complexes, thereby inhibiting scale. Organoboron compounds are environmentally friendly and can maintain good performance under high temperature conditions.

[0015] Although phosphorus-free and nitrogen-free corrosion and scale inhibitors have significant advantages in terms of environmental friendliness, they still face some challenges in practical applications:

[0016] Insufficient performance

[0017] Compared with traditional phosphorus- and nitrogen-containing corrosion and scale inhibitors, phosphorus- and nitrogen-free corrosion and scale inhibitors still have some deficiencies in performance. For example, in high-hardness and high-alkalinity water conditions, the scale inhibition effect of phosphorus- and nitrogen-free corrosion and scale inhibitors may not be as good as that of phosphorus-containing compounds. At the same time, on some metal materials, the corrosion inhibition effect of phosphorus- and nitrogen-free corrosion and scale inhibitors may also be inferior to that of traditional corrosion inhibitors.

[0018] Higher cost

[0019] Some phosphorus-free and nitrogen-free corrosion and scale inhibitors, such as polyamino acid compounds, are much more expensive than traditional corrosion and scale inhibitors due to their complex production process and high raw material costs, which to some extent limits their large-scale application.

[0020] Limited scope of application

[0021] Different types of phosphorus-free and nitrogen-free corrosion and scale inhibitors perform differently under different water quality and temperature conditions. For example, some polycarboxylic acid compounds may hydrolyze under high temperature conditions, resulting in decreased performance. Inorganic silicon compounds may precipitate under low pH conditions, affecting their corrosion and scale inhibition effects. Therefore, how to select a phosphorus-free and nitrogen-free corrosion and scale inhibitor suitable for specific working conditions remains a challenge.

[0022] Insufficient research on synergistic effects

[0023] In practical applications, multiple corrosion and scale inhibitors are usually required to be used in combination to achieve the best effect. However, the current research on the synergistic effect between phosphorus-free and nitrogen-free corrosion and scale inhibitors is not in-depth enough, which to some extent limits the improvement of their application effect.

[0024] Long-term stability needs to be improved

[0025] Some phosphorus-free and nitrogen-free corrosion and scale inhibitors, especially some natural polymer compounds, may degrade or lose performance during long-term use. How to improve the long-term stability of these green corrosion and scale inhibitors is one of the important directions for future research.

[0026] Faced with these challenges, researchers are constantly exploring new solutions:

[0027] Developing a new type of phosphorus-free and nitrogen-free corrosion and scale inhibitor

[0028] Through molecular design and synthesis of new phosphorus-free and nitrogen-free compounds, or structural modification of existing compounds, the corrosion and scale inhibition performance can be improved. For example, by introducing specific functional groups, the adsorption capacity of compounds on metal surfaces can be enhanced, thereby improving the corrosion inhibition effect.

[0029] Research on compounding technology

[0030] By studying the synergistic effects between different types of non-phosphorus and non-nitrogen corrosion and scale inhibitors, a composite formula with better performance was developed. For example, compounding polycarboxylic acid compounds with polyamino acid compounds can make up for their respective deficiencies to a certain extent and achieve performance optimization.

[0031] Nanotechnology Applications

[0032] Applying nanotechnology to the development of phosphorus-free and nitrogen-free corrosion and scale inhibitors can significantly improve their performance. For example, using nanomaterials as carriers can improve the dispersibility and stability of corrosion and scale inhibitors, thereby improving their use effect.

[0033] Research on green synthesis technology

[0034] Develop more environmentally friendly and economical green synthesis processes to reduce the production cost of phosphorus-free and nitrogen-free corrosion and scale inhibitors. For example, the use of biofermentation technology to produce polyamino acid compounds can significantly reduce production costs and improve their market competitiveness.

[0035] Development of intelligent corrosion and scale inhibition system

[0036] Combining the Internet of Things and artificial intelligence technologies, we have developed an intelligent corrosion and scale inhibition system to achieve accurate dosing and real-time monitoring of corrosion and scale inhibitors. This can not only improve the corrosion and scale inhibition effect, but also reduce the amount of chemicals used and reduce environmental impact.

[0037] In general, the development and application of phosphorus-free and nitrogen-free corrosion and scale inhibitors is a challenging but promising research field. With the continuous improvement of environmental protection requirements and the continuous advancement of technology, green and environmentally friendly corrosion and scale inhibitors will play an increasingly important role in the future industrial water treatment field. Summary of the invention

[0038] In view of this, the purpose of the present invention is to propose a green, phosphorus-free and nitrogen-free corrosion and scale inhibitor. The green, phosphorus-free and nitrogen-free corrosion and scale inhibitor of the present invention not only meets the increasingly stringent environmental protection requirements, but also has outstanding performance, applicability and economy, and provides a new type of efficient and environmentally friendly solution for the field of industrial water treatment.

[0039] The technical solutions adopted are:

[0040] A green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared from the following raw materials in parts by weight:

[0041] 10-25 parts of polyaspartic acid,

[0042] 8-18 parts of hydrolyzed polymaleic acid,

[0043] Acrylic acid / hydroxypropyl acrylate copolymer 8-20 parts,

[0044] Polyepoxysuccinic acid 10-15 parts,

[0045] 5-15 parts of delta-valerolactam,

[0046] Sodium borate 2-8 parts,

[0047] 4-8 parts of zinc sulfate heptahydrate,

[0048] Benzotriazole 0.5-1 part.

[0049] Preferably, the green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared from the following raw materials in parts by weight:

[0050] 18 parts of polyaspartic acid,

[0051] 12 parts of hydrolyzed polymaleic acid,

[0052] Acrylic acid / hydroxypropyl acrylate copolymer 14 parts,

[0053] 13 parts of polyepoxysuccinic acid,

[0054] 10 parts of delta-valerolactam,

[0055] 5 parts of sodium borate,

[0056] 6 parts of zinc sulfate heptahydrate,

[0057] 0.8 parts of benzotriazole.

[0058] Preferably, the parameters of the polyaspartic acid are: CAS number: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0059] Preferably, the parameters of the hydrolyzed polymaleic acid are: CAS number: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

[0060] Preferably, the parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0061] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0062] The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3;

[0063] The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

[0064] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0065] (1) Preparation of modified polyaspartic acid

[0066] Add polyaspartic acid to the reactor, add 60-80 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0067] Slowly add δ-valerolactam, raise the reaction temperature to 65°C-75°C, keep stirring at constant temperature for 2h-6h, and use a constant temperature water bath to keep the temperature stable;

[0068] The temperature was lowered to 50°C, benzotriazole was added, and stirring was continued for 1 h to 3 h. The reaction product was cooled to room temperature to obtain a modified polyaspartic acid solution;

[0069] (2) Addition of other components

[0070] Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0071] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0072] (3) Mixing modified polyaspartic acid with other components

[0073] The modified polyaspartic acid solution obtained in step (1) is slowly poured into the mixed solution in step (2) and continuously stirred at a constant temperature. The constant temperature stirring speed is set to 350 rpm, the constant temperature stirring time is 30 min, and the constant temperature stirring temperature is 75°C-90°C.

[0074] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0075] (4) pH adjustment and homogenization

[0076] Adjust the pH of the combined solution in step (3) to 7.5-8.5 with 0.1 M sodium hydroxide solution;

[0077] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0078] (5) Filtration and filling

[0079] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0080] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0081] In summary, the beneficial effects of the present invention are:

[0082] First of all, the corrosion and scale inhibitor adopts a phosphorus-free and nitrogen-free formula design, which meets the requirements of current environmental protection laws and policies. Traditional corrosion and scale inhibitors usually contain ingredients such as phosphates and organic phosphonates, which are easy to cause eutrophication of water bodies after being discharged into water bodies, thereby causing excessive algae growth and destroying the water ecological balance. The present invention effectively avoids this environmental problem by using phosphorus-free and nitrogen-free compounds such as polyaspartic acid, hydrolyzed polymaleic acid, acrylic acid / hydroxypropyl acrylate copolymer, etc.

[0083] Secondly, the corrosion and scale inhibitor of the present invention has excellent performance. Through reasonable component ratio and modification technology, the product can provide excellent corrosion and scale inhibition effects under various water quality conditions. The modification reaction of polyaspartic acid with δ-valerolactam and benzotriazole enhances its adsorption capacity on the metal surface, thereby improving the corrosion inhibition performance. At the same time, other components such as polyepoxysuccinic acid, hydrolyzed polymaleic acid, etc. achieve efficient scale inhibition effects by chelating metal ions and forming a protective film.

[0084] In addition, the product has good biodegradability and will not cause long-term pollution to the environment after use. Compared with traditional phosphorus-containing and nitrogen-containing corrosion and scale inhibitors, the product of the present invention does not release harmful substances during the biodegradation process, and is therefore more environmentally friendly. This feature makes it particularly suitable for application scenarios with high requirements on environmental impact, such as drinking water treatment and industrial water treatment in ecologically sensitive areas.

[0085] Finally, the method of the present invention is simple and low in cost. By optimizing the preparation process, such as homogenization and pH adjustment steps, not only the consistency and stability of the product are improved, but also the production cost is reduced. This makes the product highly competitive in commercial applications and can be widely used in circulating cooling water systems in industries such as power, petrochemicals, and metallurgy, providing these industries with an efficient, economical and environmentally friendly solution.

[0086] In summary, the present invention not only achieves a technical breakthrough, but also provides a sustainable and green solution for the field of industrial water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Figure 1 is the infrared spectrum of modified polyaspartic acid;

[0088] Figure 2 This is the XPS spectrum of modified polyaspartic acid.

[0089] Figure 3 This is a graph showing the test results of the corrosion inhibition efficiency.

[0090] Figure 4 It is a scanning electron microscope image of the carbon steel surface (the scale in the figure is 100 um, from top to bottom are blank control, comparative example 2 and embodiment 3 respectively).

[0091] Figure 5 This is the test result graph of scale inhibition rate. DETAILED DESCRIPTION

[0092] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.

[0093] Example 1

[0094] Green phosphorus-free and nitrogen-free corrosion and scale inhibitor, which is prepared from the following raw materials in parts by weight:

[0095] 10 parts of polyaspartic acid,

[0096] 18 parts of hydrolyzed polymaleic acid,

[0097] Acrylic acid / hydroxypropyl acrylate copolymer 8 parts,

[0098] 15 parts of polyepoxysuccinic acid,

[0099] 5 parts of delta-valerolactam,

[0100] 8 parts of sodium borate,

[0101] 4 parts of zinc sulfate heptahydrate,

[0102] 1 part of benzotriazole.

[0103] The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0104] The parameters of the hydrolyzed polymaleic acid are: CAS No.: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

[0105] The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0106] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0107] The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3;

[0108] The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

[0109] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0110] (1) Preparation of modified polyaspartic acid

[0111] Add polyaspartic acid to the reactor, add 60 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0112] Slowly add δ-valerolactam, raise the reaction temperature to 65°C, keep stirring at constant temperature for 6 hours, and use a constant temperature water bath to keep the temperature stable;

[0113] The temperature was lowered to 50°C, benzotriazole was added, and stirring was continued for 1 hour. The reaction product was cooled to room temperature to obtain a modified polyaspartic acid solution;

[0114] (2) Addition of other components

[0115] Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0116] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0117] (3) Mixing modified polyaspartic acid with other components

[0118] The modified polyaspartic acid solution obtained in step (1) was slowly poured into the mixed solution in step (2) and continuously stirred at a constant temperature. The constant temperature stirring speed was set to 350 rpm, the constant temperature stirring time was 30 min, and the constant temperature stirring temperature was 75°C.

[0119] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0120] (4) pH adjustment and homogenization

[0121] Adjust the pH of the combined solution in step (3) to 7.5 with 0.1 M sodium hydroxide solution;

[0122] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0123] (5) Filtration and filling

[0124] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0125] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0126] Example 2

[0127] Green phosphorus-free and nitrogen-free corrosion and scale inhibitor, which is prepared from the following raw materials in parts by weight:

[0128] 25 parts of polyaspartic acid,

[0129] 8 parts of hydrolyzed polymaleic acid,

[0130] Acrylic acid / hydroxypropyl acrylate copolymer 20 parts,

[0131] 10 parts of polyepoxysuccinic acid,

[0132] 15 parts of delta-valerolactam,

[0133] 2 parts of sodium borate,

[0134] 8 parts of zinc sulfate heptahydrate,

[0135] 0.5 parts of benzotriazole.

[0136] The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0137] The parameters of the hydrolyzed polymaleic acid are: CAS No.: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

[0138] The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0139] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0140] The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3;

[0141] The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

[0142] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0143] (1) Preparation of modified polyaspartic acid

[0144] Add polyaspartic acid to the reactor, add 80 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0145] Slowly add δ-valerolactam, raise the reaction temperature to 75°C, keep stirring at constant temperature for 2 hours, and use a constant temperature water bath to keep the temperature stable;

[0146] The temperature was lowered to 50°C, benzotriazole was added, and stirring was continued for 3 hours. The reaction product was cooled to room temperature to obtain a modified polyaspartic acid solution;

[0147] (2) Addition of other components

[0148] Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0149] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0150] (3) Mixing modified polyaspartic acid with other components

[0151] The modified polyaspartic acid solution obtained in step (1) was slowly poured into the mixed solution in step (2), and constant temperature stirring was continued. The constant temperature stirring speed was set to 350 rpm, the constant temperature stirring time was 30 min, and the constant temperature stirring temperature was 90°C.

[0152] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0153] (4) pH adjustment and homogenization

[0154] Adjust the pH of the combined solution in step (3) to 8.5 with 0.1 M sodium hydroxide solution;

[0155] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0156] (5) Filtration and filling

[0157] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0158] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0159] Example 3

[0160] Green phosphorus-free and nitrogen-free corrosion and scale inhibitor, which is prepared from the following raw materials in parts by weight:

[0161] 18 parts of polyaspartic acid,

[0162] 12 parts of hydrolyzed polymaleic acid,

[0163] Acrylic acid / hydroxypropyl acrylate copolymer 14 parts,

[0164] 13 parts of polyepoxysuccinic acid,

[0165] 10 parts of delta-valerolactam,

[0166] 5 parts of sodium borate,

[0167] 6 parts of zinc sulfate heptahydrate,

[0168] 0.8 parts of benzotriazole.

[0169] The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0170] The parameters of the hydrolyzed polymaleic acid are: CAS No.: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

[0171] The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0172] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0173] The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3;

[0174] The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

[0175] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0176] (1) Preparation of modified polyaspartic acid

[0177] Add polyaspartic acid to the reactor, add 70 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0178] Slowly add δ-valerolactam, raise the reaction temperature to 70°C, keep stirring at constant temperature for 4 hours, and use a constant temperature water bath to keep the temperature stable;

[0179] The temperature was lowered to 50°C, benzotriazole was added, and stirring was continued for 2 hours. The reaction product was cooled to room temperature to obtain a modified polyaspartic acid solution;

[0180] (2) Addition of other components

[0181] Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0182] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0183] (3) Mixing modified polyaspartic acid with other components

[0184] The modified polyaspartic acid solution obtained in step (1) was slowly poured into the mixed solution in step (2) and continuously stirred at a constant temperature. The constant temperature stirring speed was set to 350 rpm, the constant temperature stirring time was 30 min, and the constant temperature stirring temperature was 85°C.

[0185] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0186] (4) pH adjustment and homogenization

[0187] Adjust the pH of the combined solution in step (3) to 8 with 0.1 M sodium hydroxide solution;

[0188] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0189] (5) Filtration and filling

[0190] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0191] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0192] Comparative Example 1

[0193] Green phosphorus-free and nitrogen-free corrosion and scale inhibitor, which is prepared from the following raw materials in parts by weight:

[0194] 18 parts of polyaspartic acid,

[0195] Acrylic acid / hydroxypropyl acrylate copolymer 14 parts,

[0196] 13 parts of polyepoxysuccinic acid,

[0197] 10 parts of delta-valerolactam,

[0198] 5 parts of sodium borate,

[0199] 6 parts of zinc sulfate heptahydrate,

[0200] 0.8 parts of benzotriazole.

[0201] The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0202] The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0203] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0204] The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3;

[0205] The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

[0206] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0207] (1) Preparation of modified polyaspartic acid

[0208] Add polyaspartic acid to the reactor, add 70 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0209] Slowly add δ-valerolactam, raise the reaction temperature to 70°C, keep stirring at constant temperature for 4 hours, and use a constant temperature water bath to keep the temperature stable;

[0210] The temperature was lowered to 50°C, benzotriazole was added, and stirring was continued for 2 hours. The reaction product was cooled to room temperature to obtain a modified polyaspartic acid solution;

[0211] (2) Addition of other components

[0212] Add acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0213] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0214] (3) Mixing modified polyaspartic acid with other components

[0215] The modified polyaspartic acid solution obtained in step (1) was slowly poured into the mixed solution in step (2) and continuously stirred at a constant temperature. The constant temperature stirring speed was set to 350 rpm, the constant temperature stirring time was 30 min, and the constant temperature stirring temperature was 85°C.

[0216] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0217] (4) pH adjustment and homogenization

[0218] Adjust the pH of the combined solution in step (3) to 8 with 0.1 M sodium hydroxide solution;

[0219] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0220] (5) Filtration and filling

[0221] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0222] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0223] Comparative Example 2

[0224] Green phosphorus-free and nitrogen-free corrosion and scale inhibitor, which is prepared from the following raw materials in parts by weight:

[0225] 18 parts of polyaspartic acid,

[0226] 12 parts of hydrolyzed polymaleic acid,

[0227] Acrylic acid / hydroxypropyl acrylate copolymer 14 parts,

[0228] 13 parts of polyepoxysuccinic acid,

[0229] 5 parts of sodium borate,

[0230] 6 parts of zinc sulfate heptahydrate,

[0231] 0.8 parts of benzotriazole.

[0232] The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0233] The parameters of the hydrolyzed polymaleic acid are: CAS No.: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

[0234] The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0235] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0236] The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

[0237] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0238] (1) Preparation of modified polyaspartic acid

[0239] Add polyaspartic acid to the reactor, add 70 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0240] Add benzotriazole, continue stirring for 2 hours, and cool the reaction product to room temperature to obtain a modified polyaspartic acid solution;

[0241] (2) Addition of other components

[0242] Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0243] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0244] (3) Mixing modified polyaspartic acid with other components

[0245] The modified polyaspartic acid solution obtained in step (1) was slowly poured into the mixed solution in step (2) and continuously stirred at a constant temperature. The constant temperature stirring speed was set to 350 rpm, the constant temperature stirring time was 30 min, and the constant temperature stirring temperature was 85°C.

[0246] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0247] (4) pH adjustment and homogenization

[0248] Adjust the pH of the combined solution in step (3) to 8 with 0.1 M sodium hydroxide solution;

[0249] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0250] (5) Filtration and filling

[0251] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0252] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0253] Comparative Example 3

[0254] Green phosphorus-free and nitrogen-free corrosion and scale inhibitor, which is prepared from the following raw materials in parts by weight:

[0255] 18 parts of polyaspartic acid,

[0256] 12 parts of hydrolyzed polymaleic acid,

[0257] Acrylic acid / hydroxypropyl acrylate copolymer 14 parts,

[0258] 13 parts of polyepoxysuccinic acid,

[0259] 10 parts of delta-valerolactam,

[0260] 5 parts of sodium borate,

[0261] 6 parts of zinc sulfate heptahydrate.

[0262] The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

[0263] The parameters of the hydrolyzed polymaleic acid are: CAS No.: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

[0264] The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

[0265] The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

[0266] The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3.

[0267] The green phosphorus-free and nitrogen-free corrosion and scale inhibitor is prepared by the following method:

[0268] (1) Preparation of modified polyaspartic acid

[0269] Add polyaspartic acid to the reactor, add 70 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved;

[0270] Slowly add δ-valerolactam, raise the reaction temperature to 70°C, keep constant temperature stirring for 4 hours, use a constant temperature water bath to keep the temperature stable, and cool the reaction product to room temperature to obtain a modified polyaspartic acid solution;

[0271] (2) Addition of other components

[0272] Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly;

[0273] Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution;

[0274] (3) Mixing modified polyaspartic acid with other components

[0275] The modified polyaspartic acid solution obtained in step (1) was slowly poured into the mixed solution in step (2) and continuously stirred at a constant temperature. The constant temperature stirring speed was set to 350 rpm, the constant temperature stirring time was 30 min, and the constant temperature stirring temperature was 85°C.

[0276] During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid;

[0277] (4) pH adjustment and homogenization

[0278] Adjust the pH of the combined solution in step (3) to 8 with 0.1 M sodium hydroxide solution;

[0279] The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min;

[0280] (5) Filtration and filling

[0281] Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities;

[0282] The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

[0283] test

[0284] Taking the product prepared in Example 3 as an example, the infrared spectrum of the modified polyaspartic acid is as follows: Figure 1 As shown, and its XPS spectrum is as follows Figure 2 shown.

[0285] Next, a corrosion inhibition experiment was carried out. A3 carbon steel specimens (50mm×25mm×2mm) with known weight (accurate to 0.0001g) were immersed in a beaker filled with 500mL of tap water (seven groups were set up with a concentration of 400mg / L, namely blank control, Example 1-3, and Comparative Example 1-3) and placed at 80°C for 72h. Then, the A3 carbon steel specimens were cleaned with a solution of 10g / L hexamethylenetetramine in 3mol / LHCl, distilled water, 60g / L NaOH solution, distilled water and ethanol, respectively. The A3 sheet was dried and weighed, and the corrosion inhibition efficiency of the inhibitor was calculated respectively (refer to https: / / do i.org / 10.1071 / CH16720). As Figure 3 As shown, it can be seen that the anti-corrosion inhibition efficiency of Examples 1-3 of the present invention is as high as 88.6%, while the anti-corrosion inhibition efficiency of Comparative Example 1 is 82.1%, the anti-corrosion inhibition efficiency of Comparative Example 2 is 67.5%, and the anti-corrosion inhibition efficiency of Comparative Example 3 is 73.2%. Figure 4 It can be seen that the carbon steel surface corrosion caused by Example 3 is the mildest.

[0286] Finally, the scale inhibition performance was tested by sequentially adding 20.0 mL of CaCl2 solution (c = 16.7 g / L), antifouling agent (seven groups with a concentration of 400 mg / L, namely blank control, Example 1-3, Comparative Example 1-3), 20.0 mL of borax buffer (pH = 9.0) and 20.0 mL of NaHCO3 solution (c = 25.2 g / L) into 250 mL of distilled water. The solution was diluted to 500.0 mL. At this time, CaCl2 solution was added to the mixture. 2 + concentration is about 240mg / L. Then, the solution was transferred to a conical flask for deposition experiment. The temperature was kept constant at 60, 70 and 80℃ for 10 hours respectively. Ca 2 The concentration of + is determined by EDTA titration method, and the scale inhibition rate is calculated by reference to "do i:10.3390 / ma12111821". Figure 5 As shown, the scale inhibition rates of Examples 1-3 range from 90.5% to 92.4%, and the scale inhibition rates of Comparative Examples 1-3 are 83.0%, 63.8% and 74.2%, respectively.

[0287] The green, phosphorus-free, nitrogen-free corrosion and scale inhibitor of the present invention has significant advantages in corrosion inhibition and scale prevention, mainly for the following reasons:

[0288] Corrosion inhibition performance

[0289] Ingredient design: The invention adopts ingredients such as polyaspartic acid, δ-valerolactam and benzotriazole, which significantly enhance the adsorption capacity of metals by forming a protective film on the metal surface, thereby improving the corrosion inhibition performance.

[0290] Experimental results: The embodiment shows that the anti-corrosion inhibition efficiency is as high as 88.6%, which is significantly better than the results of the comparative example experiment (such as 67.5% in comparative example 2).

[0291] Anti-fouling performance

[0292] Chelation and film formation: Hydrolyzed components such as polymaleic acid and polyepoxysuccinic acid effectively prevent the formation of scale by chelating metal ions and forming a protective film.

[0293] Experimental verification: The test results show that the scale inhibition rate of the embodiment is between 90.5% and 92.4%, which is significantly higher than that of the comparative example (eg, 63.8% for comparative example 2).

[0294] Advantages

[0295] Environmental protection: The invention does not contain phosphorus and nitrogen, avoiding the eutrophication problem of water bodies caused by traditional corrosion and scale inhibitors, and complies with environmental protection regulations.

[0296] Biodegradability: It will not cause long-term pollution to the environment after use and is more environmentally friendly than traditional products.

[0297] Economy and process simplicity: By optimizing the preparation process, the production cost is reduced, the consistency and stability of the product are improved, making it competitive in commercial applications.

[0298] Meanwhile, the analysis of Examples 1-3 is as follows:

[0299] Based on the information provided, we can analyze the influence mechanism of the removal of different components on the corrosion and scale inhibition performance of these three comparative examples:

[0300] Comparative Example 1: Removal of hydrolyzed polymaleic acid

[0301] The removal of hydrolyzed polymaleic acid has a significant effect on the corrosion and scale inhibition performance: hydrolyzed polymaleic acid is an excellent scale inhibitor, and its main mechanism of action is: through the carboxyl group and metal ions (such as Ca 2 +、Mg 2+) to form a soluble complex to prevent scaling. It adsorbs at the crystal growth point, interferes with the crystallization process, and inhibits the growth of scale crystals. Although hydrolyzed polymaleic acid mainly acts on scale inhibition, it can also form a protective film on the metal surface to synergistically improve the corrosion inhibition effect.

[0302] Comparative Example 2: Removal of δ-valerolactam

[0303] The removal of δ-valerolactam has a significant impact on the corrosion inhibition performance: δ-valerolactam is an important corrosion inhibitor, and its mechanism of action includes: forming coordination bonds with the metal surface through nitrogen atoms to enhance adsorption capacity. Forming a dense protective film to block the contact between corrosive media and the metal surface. δ-valerolactam can produce a synergistic effect with polyaspartic acid to jointly improve the corrosion inhibition performance. After removal, this synergistic effect disappears, resulting in a decrease in overall performance.

[0304] Comparative Example 3: Removal of benzotriazole

[0305] The removal of benzotriazole has a certain impact on the corrosion inhibition performance:

[0306] Benzotriazole is a highly effective corrosion inhibitor, and its mechanism of action includes: forming a stable protective film through coordination bonds between nitrogen atoms and metal surfaces. It has strong adsorption capacity and can effectively block corrosive media. Weakened synergistic effect: Benzotriazole can produce synergistic effects with other components (such as polyaspartic acid and δ-valerolactam) to improve the overall corrosion inhibition performance. After removal, this synergistic effect is weakened.

[0307] In addition, δ-valerolactam enhances the corrosion inhibition performance of polyaspartic acid mainly through the following ways: Increase adsorption capacity: The nitrogen atoms in δ-valerolactam can form hydrogen bonds with polyaspartic acid, improve the adsorption capacity of polyaspartic acid on the metal surface, and thus enhance the corrosion inhibition effect. Form a protective film: δ-valerolactam can form a dense protective film on the metal surface, blocking the contact between corrosive media and metals, and play a physical shielding role. Synergistic effect: The synergistic effect of δ-valerolactam and polyaspartic acid can further improve the corrosion inhibition performance. Benzotriazole mainly enhances the corrosion inhibition performance of polyaspartic acid through the following mechanisms: Form a coordination bond: The three nitrogen atoms in benzotriazole can form a stable coordination bond with the metal surface, enhance the adsorption capacity, and form a dense protective film. Improve the film density: The addition of benzotriazole can improve the density of the protective film formed by polyaspartic acid and enhance the physical shielding effect. Synergistic effect: The synergistic effect of benzotriazole, polyaspartic acid and δ-valerolactam can further enhance the overall corrosion inhibition performance.

[0308] In summary, the addition of δ-valerolactam and benzotriazole significantly improved the corrosion inhibition performance of polyaspartic acid by enhancing adsorption capacity, forming a dense protective film, and producing a synergistic effect. This reflects the innovation of the present invention in molecular design and modification strategy.

[0309] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A green, phosphorus-free and nitrogen-free corrosion and scale inhibitor, characterized in that: It is prepared from the following raw materials in parts by weight: 10-25 parts of polyaspartic acid, 8-18 parts of hydrolyzed polymaleic acid, 8-20 parts of acrylic acid / hydroxypropyl acrylate copolymer, Polyepoxysuccinic acid 10-15 parts, 5-15 parts of delta-valerolactam, Sodium borate 2-8 parts, 4-8 parts of zinc sulfate heptahydrate, Benzotriazole 0.5-1 part.

2. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight: 18 parts of polyaspartic acid, 12 parts of hydrolyzed polymaleic acid, Acrylic acid / hydroxypropyl acrylate copolymer 14 parts, 13 parts of polyepoxysuccinic acid, 10 parts of delta-valerolactam, 5 parts of sodium borate, 6 parts of zinc sulfate heptahydrate, 0.8 parts of benzotriazole.

3. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 2, characterized in that: The parameters of the polyaspartic acid are: CAS No.: 25608-40-6, molecular weight: 133.103 g / mol, density: 1.5±0.1 g / cm3.

4. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 2, characterized in that: The parameters of the hydrolyzed polymaleic acid are: CAS No.: 26099-09-2, molecular weight: between 800 and 1000, appearance: brown-red transparent liquid, density: 1.18 g / cm3.

5. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 2, characterized in that: The parameters of the acrylic acid / hydroxypropyl acrylate copolymer are: CAS No.: 55719-33-0, molecular weight: 202.21, density: 1.15±0.05, appearance: light yellow transparent liquid.

6. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 2, characterized in that: The parameters of the polyepoxysuccinic acid are: CAS No.: 1528-98-71, density: 1.15 g / cm3.

7. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 2, characterized in that: The parameters of the δ-valerolactam are: CAS No.: 675-20-7, density: 1.073 g / cm3; The parameters of the benzotriazole are: CAS No.: 95-14-7, density: 1.3±0.1 g / cm3.

8. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 2, characterized in that: It is prepared by the following method: (1) Preparation of modified polyaspartic acid Add polyaspartic acid to the reactor, add 60-80 times the mass of deionized water and stir at a stirring speed of 300 rpm until completely dissolved; Slowly add δ-valerolactam, raise the reaction temperature to 65°C-75°C, keep stirring at constant temperature for 2h-6h, and use a constant temperature water bath to keep the temperature stable; The temperature was lowered to 50°C, benzotriazole was added, and stirring was continued for 1 h to 3 h. The reaction product was cooled to room temperature to obtain a modified polyaspartic acid solution; (2) Addition of other components Add hydrolyzed polymaleic acid and acrylic acid / hydroxypropyl acrylate copolymer into another reaction kettle, set the stirring speed to 250 rpm, and stir evenly; Slowly add polyepoxysuccinic acid and continue stirring until the solution becomes clear and transparent to obtain a mixed solution; (3) Mixing modified polyaspartic acid with other components Slowly pour the modified polyaspartic acid solution obtained in step (1) into the mixed solution in step (2), and continue to stir at a constant temperature, wherein the constant temperature stirring speed is set to 350 rpm and the constant temperature stirring time is 30 min; During the stirring process, sodium borate and zinc sulfate heptahydrate are added in sequence, and stirring is continued until they are completely dissolved without precipitation, thereby obtaining a combined liquid; (4) pH adjustment and homogenization Adjust the pH of the combined solution in step (3) to 7.5-8.5 with 0.1 M sodium hydroxide solution; The combined solution was transferred to a high-speed disperser and homogenized at 5000 rpm for 30 min; (5) Filtration and filling Filter the homogenized solution in step (4) using a 100-mesh sieve to remove insoluble matter and impurities; The filtered product is filled into dry, clean and sealed containers and tested for corrosion and scale inhibition performance to ensure that the product meets the expected standards.

9. The green phosphorus-free and nitrogen-free corrosion and scale inhibitor according to claim 8, characterized in that: The temperature of the constant temperature stirring in step (3) is 75°C-90°C.

Citation Information

Patent Citations

  • No-phosphate corrosion and scale inhibitor and its application

    CN101066811A

  • Phosphorus-free composite scale-inhibiting corrosion-retarding agent and application thereof in water treatment

    CN102452721A

  • Non-phosphorus compound scale and corrosion inhibitor for treatment of circulating cooling water

    CN1621362A

  • Non-Phosphorus composite anti incrustation eorrosion snhibiter and its application in water treatment

    CN1785853A

  • Phosphorus-free corrosion and scale inhibitor used in circulating cooling water of central air conditioning and its preparation method

    US20160318783A1

Cited By

  • Phosphorus-free corrosion inhibition water treatment agent and preparation method thereof

    CN119461678A

  • Preparation method of corrosion and scale inhibitor

    CN119570524A

  • Preparation method of corrosion and scale inhibitor

    CN119570524B

  • Biochemically degradable phosphorus-free nitrogen-free scale inhibitor

    CN119660978A